Hands-on meta learning with Python : meta learning using one-shot learning, MAML, Reptile, and Meta-SGD with TensorFlow /: meta learning using one-shot learning, MAML, Reptile, and Meta-SGD with TensorFlow. (2018) - Ravichandiran, Sudharsan
No abstract available